Efficacy and Safety of Dipyrone Versus Tramadol in the Management of Pain After Hysterectomy: A Randomized, Double-Blind, Multicenter Study. Issue 2 (1st March 2001) - Torres, Luis M.; Rodríguez, Manuel J.; Montero, Antonio; Herrera, Jeronimo; Calderón, Enrique; Cabrera, Jesus; Porres, Rocio; de la Torre, Rosalia M.; Martínez, Tomas; Gómez, Jose L.; Ruiz, Jorge; García-Magaz, Inmaculada; et al.
Abstract : Background and Objectives: We assessed the efficacy and safety of dipyrone in comparison with tramadol in the relief of early postoperative pain following abdominal hysterectomy. Methods: A total of 151 women between 18 and 60 years of age undergoing abdominal hysterectomy during general anesthesia participated in a randomized, double-blind, controlled, multicenter study. Seventy-three patients received dipyrone and 78 received tramadol. Patients received an intravenous loading dose of the study drug immediately after operation followed by intravenous (IV) maintenance infusion and IV on-demand boluses up to a maximum number of predetermined doses/day of 8 g dipyrone and 500 mg tramadol. The duration of the study was 24 hours. Results: The mean (SD) number of boluses in the dipyrone group was 3.8 (2.4) and 3.5 (2.5) in the tramadol group (95% confidence interval, −0.455 to 1.175), and the percentage of patients requiring rescue IV morphine (dipyrone 26.9%, tramadol 26.8%) was not statistically significant. Other analgesic efficacy parameters, such as pain intensity differences, sum of pain intensity differences, pain relief assessed by the patient, or patients who required the maximum number of demand doses, were not different between treatment groups. A significantly higher percentage of adverse gastrointestinal effects was found in patients given tramadol (42.1%) than in patients given dipyrone (20.2%) ( P < .05). Also, a significantly higher number of tramadol-treated patients required ondansetron to control nausea and vomiting at 1 hour (19% v 7%), 2 hours (26% v 11%), and 24 hours (46% v 29%) ( P < .05) after surgery. Patients and the investigators reported similar tolerability for both study arms. Conclusions: Dipyrone and tramadol showed similar efficacy for early pain relief after abdominal hysterectomy. Nausea and vomiting, possibly caused by the tramadol, occurred more frequently in those patients. In this group, the need of the antiemetic drug ondansetron was also higher.